2014
DOI: 10.1007/s13197-014-1338-2
|View full text |Cite
|
Sign up to set email alerts
|

Rheology, fatty acid profile and quality characteristics of nutrient enriched pizza base

Abstract: Enrichment of thick bread type pizza base (PZB) was done by substituting wheat flour (WF) with 5, 10 and 15 % soya protein isolate (SPI). The rheological characteristics of WF showed that water absorption increased, extensibility and peak viscosity decreased when level of SPI increased from 5 to 15 %. Baking studies showed that spread ratio decreased and hardness values of PZB increased with the increase in amount of SPI from 5 to15 %. Beyond 10 % SPI, the overall quality of PZB was adversely affected. To the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
7
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 26 publications
2
7
0
2
Order By: Relevance
“…These findings are in line with the report published by Gupta et al. (2015) on their study on soy protein isolate incorporated PB. Similarly, The use of CA significantly improved the physical characteristics of PB except for hunter color values.…”
Section: Resultssupporting
confidence: 93%
See 3 more Smart Citations
“…These findings are in line with the report published by Gupta et al. (2015) on their study on soy protein isolate incorporated PB. Similarly, The use of CA significantly improved the physical characteristics of PB except for hunter color values.…”
Section: Resultssupporting
confidence: 93%
“…Similar results were reported for nutrient‐enriched PB containing soy protein isolates and psyllium husk by Gupta et al. (2015). They reported that the addition of 10% soy protein isolate and 5% psyllium husk to wheat flour increased the ash (2.50–2.80%) protein content (8.50–14.50%), and dietary fiber content (4.90–8.00%), respectively, in the pizza base.…”
Section: Resultssupporting
confidence: 89%
See 2 more Smart Citations
“…The seeds known as psyllium are mainly sourced from black Plantago psyllium and blond Plantago ovata [ 1 ]. Plantago products are source of dietary fiber with a high proportion of water-soluble fraction having gel-forming properties [ 2 , 3 , 4 ]. Its effect on the human body includes cholesterol-lowering effect, laxative and glycemic index reduction [ 2 , 4 , 5 , 6 , 7 ].…”
Section: Introductionmentioning
confidence: 99%